Policy and Practice Review: A First Guideline on the Use of Pharmacogenetics in Clinical Psychiatric Practice - van Westrhenen, R.; van Schaik, R. H. N.; van Gelder, T.; Birkenhager, T. K.; Bakker, P. R.; Houwink, E. J. F.; Bet, P. M.; Hoogendijk, W. J. G.; van Weelden-Hulshof, M. J. M. (Frontiers in Pharmacology, 2021)
Effective pharmacologic treatments for psychiatric disorders are available, but their effect is limited due to patients’ genetic heterogeneity and low compliance-related to frequent adverse events. Only one third of patients respond to treatment and experience remission. Pharmacogenetics is a relatively young field which focusses on the genetic analyses in the context of the metabolism and outcome of drug treatment. These genetic factors can, among other things, lead to differences in the activity of enzymes that metabolize drugs. Recently, a clinical guideline was composed by the Dutch Clinical Psychiatric Association (NVvP) on the clinical use of pharmacogenetics in psychiatry. The main goal was to provide guidance, based on current evidence, on how to best use genotyping in clinical psychiatric practice. A systematic literature search was performed, and available publications were assessed using the GRADE methodology. General recommendations for psychiatric clinical practice were provided, and specific recommendations per medication were made available. This clinical guideline for caregivers prescribing psychotropic drugs is the product of a broad collaboration of professionals from different disciplines, making use of the information available at the Dutch Pharmacogenetics Working Group (DPWG) and the Clinical Pharmacogenetics Implementation Consortium (CPIC) so far. We summarize the relevant literature and all recommendations in this article. General recommendations are provided and also detailed recommendations per medication. In summary we advise to consider genotyping, when there are side effects or inefficacy for CYP2C9 and CYP2D6. When genotype information is available use this to select the right drug in the right dose for the right patient.